امتِ مسلمہ کو درپیش جدید علمی تحدیات : ابن رشد کے افکار سے رہنمائی (Al-Qamar, 2023)
Nowadays, the Muslim Ummah is facing many problems in the field of knowledge, Science and Philosophy. The Muslim world is intellectually backward compared to the West. There is no legitimate pursuit of education and research in influential and wealthy Muslim countries. In addition, Muslim societies are divided into classes in Education Sector. Ancient and modern educational institutions have become antagonistic to each other. Although efforts have been made to harmonize ancient and modern education, but since the beginning of the new century, the educational revolution has come, institutions of higher learning have been established. New research and academic fields and disciplines have been introduced. For this reason, there have been many effects on Muslim thought. In the passion of research, students are shown the path of Skepticism, Deviation and Atheism.  The people of Andalusia were high in knowledge and grace, but Averroes thought several centuries ahead. He was like a modern man who had gone back in time. He is an important Muslim Scholar of the 12th century; he described the usefulness of the continuation of education and research in his books, and tried to connect the scholars with knowledge and wisdom, according to him, it helps to reach God. He explained the utility of Philosophy and wisdom and considered it to a hope for the mankind. Averroes was engrossed in the search for scientific facts and laws of nature and wanted to see the knowledge by religion and reason as harmonious, so that there should be no deep division in the sciences. He drew attention to the teacher adopting the teaching methods according to the mind of the student. He called for faith and belief, and he wanted to keep high-level research within the reach of those who can use these sciences to protect themselves from the evil in their hearts and minds. On the contrary, strange dangers may arise, as he rejected the Atheism and Skepticism. Averroes highlights the importance of acquiring knowledge in the interests of the Muslim Ummah. He acknowledged the supremacy of the divine philosopher and talked about the importance of scientific and research evidence, if the research had continued on this basis, the Muslim Ummah would not have suffered stagnation and decline. Even today, Averroes’ research is a guide for the Muslim Ummah. By considering him, Muslims can regain their lost position. This research has shown that his ideas are the guide in contemporary intellectual problems, and should be solved.
Keywords: Atheism; Averroes; Deviation; Education; Skepticism; Ummah